2001
DOI: 10.1159/000047642
|View full text |Cite
|
Sign up to set email alerts
|

Prestroke Dementia

Abstract: Objective: To determine the frequency, associated factors and outcome of dementia previous to a stroke. Design: Cross-sectional study of a cohort of 324 consecutive unselected stroke patients (mean age 70.9 years, range 20–98; 255 ischaemic, 46 haemorrhagic and 25 indefinite). Methods: Cognitive and functional status prior to stroke were assessed by means of an interview to a relative, a short version of the Informant Questionnaire on Cognitive Decline in the Elderly and the Barthel Index. The DSM-III-R criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
40
2
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 23 publications
6
40
2
4
Order By: Relevance
“…For this longitudinal study, we excluded 63 patients (19.2%) who died before the third month after stroke, 32 (9.8%) who were demented before stroke, 6 and 39 (11.9%) who did not attend any of the scheduled follow-up visits (29; 8.8%) or had an inadequate baseline evaluation (10; 3%). The present prospective study included 193 patients.…”
Section: Patientsmentioning
confidence: 99%
“…For this longitudinal study, we excluded 63 patients (19.2%) who died before the third month after stroke, 32 (9.8%) who were demented before stroke, 6 and 39 (11.9%) who did not attend any of the scheduled follow-up visits (29; 8.8%) or had an inadequate baseline evaluation (10; 3%). The present prospective study included 193 patients.…”
Section: Patientsmentioning
confidence: 99%
“…[12][13][14] Hospital based 15 and population based studies 16 have shown that patients with dementia have an increased risk of seizures compared with the general population. However, the question of whether stroke patients with pre-existing dementia are at increased risk for poststroke seizures has never been investigated.…”
mentioning
confidence: 99%
“…6 -14 Recent studies have also demonstrated that many stroke patients seem to have preexisting cognitive decline, and one sixth of them have previous dementia. [15][16][17] Dementia is a cause of morbidity/mortality in the elderly and is a risk factor for adverse outcomes; it reduces life expectancy independently of its etiology. 18,19 In a previous study, Tatemichi et al 20 demonstrated that dementia adversely influences long-term survival after stroke; however, it is unknown whether mortality is determined by dementia that precedes stroke or that appears just after it.…”
mentioning
confidence: 99%